The Longest Night Three Generations of Chinese Trotskyists in Defeat, Jail, Exile, and Diaspora - Benton, Gregor 1944- (BRILL, 2024)
The Longest Night is a sequel to Prophets Unarmed (Brill 2014), a sourcebook on early Chinese Trotskyism. The present volume continues the story of Chinese Trotskyism beyond 1949, the year of Mao Zedong's victory at national level and of the Trotskyists' imminent destruction. Its title is drawn from a poem by the Chinese Trotskyist leader Zheng Chaolin conceived in prison in 1952.
Description based on publisher supplied metadata and other sources
Keywords: Trotsky, Leon / 1879-1940; Communism / China / History; Communists / China / Biography